2000
DOI: 10.1103/physreve.61.5171
|View full text |Cite
|
Sign up to set email alerts
|

Hamiltonian dynamics and geometry of phase transitions in classicalXYmodels

Abstract: The Hamiltonian dynamics associated to classical, planar, Heisenberg XY models is investigated for two-and three-dimensional lattices. Besides the conventional signatures of phase transitions, here obtained through time averages of thermodynamical observables in place of ensemble averages, qualitatively new information is derived from the temperature dependence of Lyapunov exponents. A Riemannian geometrization of newtonian dynamics suggests to consider other observables of geometric meaning tightly related wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…Several results strongly support this Topological Hypothesis and suggest that a phase transition might well be the consequence of an abrupt transition between different rates of change in the topology above and below the critical point. More details can be found in the review paper [36] and in the subsequent papers: [58] where the topology of the M v is analytically studied for the mean-field XY model; [59,60] where the topology of the M v is analytically studied for a trigonometric model undergoing also a first-order phase transition; [60,61] where an analytic relationship between topology and thermodynamic entropy is given among other results; [62,63] where a preliminary account of a general theorem on topology and phase transitions is given.…”
Section: Hamiltonian Dynamics Phase Transitions and Topologymentioning
confidence: 99%
“…Several results strongly support this Topological Hypothesis and suggest that a phase transition might well be the consequence of an abrupt transition between different rates of change in the topology above and below the critical point. More details can be found in the review paper [36] and in the subsequent papers: [58] where the topology of the M v is analytically studied for the mean-field XY model; [59,60] where the topology of the M v is analytically studied for a trigonometric model undergoing also a first-order phase transition; [60,61] where an analytic relationship between topology and thermodynamic entropy is given among other results; [62,63] where a preliminary account of a general theorem on topology and phase transitions is given.…”
Section: Hamiltonian Dynamics Phase Transitions and Topologymentioning
confidence: 99%
“…This can be achieved by improving some preliminary results on the subject reported in [22,23]. Consider a generic classical system described by a Hamiltonian…”
Section: Topology and Thermodynamics: A Direct Linkmentioning
confidence: 99%
“…We have thus shown that as v changes from its minimum −h (corresponding to n π = 0) to 1 2 (corresponding to n π = N 2 ) the manifolds M v undergo a sequence of topology changes at the N critical values v(n π ) given by Eq. (9). There might be a TC also at the last (maximum) critical value v c = 1 2 + h 2 2 .…”
Section: Pacs Number(s)mentioning
confidence: 99%
“…This is the more surprising since in many cases, knowing a priori that a system undergoes a PT, several relevant properties of the PT can be predicted just in terms of very general features of V (ϕ) (e.g., by means of renormalization-group techniques). In the light of some recent results [5][6][7][8][9][10][11] an alternative new approach approach seems actually possible by resorting to topological concepts: PTs would then be related to topology changes (TCs) of suitable submanifolds of configuration space, defined by the potential energy V (ϕ). The connection between topology of configuration space and PTs can be heuristically understood as follows.…”
mentioning
confidence: 99%